2016
DOI: 10.1186/s12883-016-0610-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of rotigotine transdermal patch for the treatment of apathy and motor symptoms in Parkinson’s disease

Abstract: BackgroundThis multicenter, double-blind, placebo-controlled study assessed the efficacy of rotigotine transdermal patch on apathy and motor symptoms in patients with Parkinson’s disease (PD).MethodsPatients with PD-associated apathy (Unified Parkinson's Disease Rating Scale [UPDRS] I item 4 [motivation] ≥2 and patient-rated Apathy Scale [AS] ≥14) were randomized 1:1:1 to “low-dose” rotigotine (≤6 mg/24 h for early PD [those not receiving levodopa] or ≤8 mg/24 h for advanced PD [those receiving levodopa]), “hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 25 publications
1
35
0
6
Order By: Relevance
“…New positive studies evaluated pramipexole immediate release (IR) and pramipexole extended release (ER), and the practice implication remains “clinically useful.” An extension study using pramipexole ER reported no new safety concerns. A total of 2 new positive studies evaluating rotigotine also confirmed the practice implication of “clinically useful.” There are no new safety concerns with any of these drug preparations.…”
Section: Results and Conclusionmentioning
confidence: 81%
See 1 more Smart Citation
“…New positive studies evaluated pramipexole immediate release (IR) and pramipexole extended release (ER), and the practice implication remains “clinically useful.” An extension study using pramipexole ER reported no new safety concerns. A total of 2 new positive studies evaluating rotigotine also confirmed the practice implication of “clinically useful.” There are no new safety concerns with any of these drug preparations.…”
Section: Results and Conclusionmentioning
confidence: 81%
“…High‐quality studies reported positive outcomes for pramipexole ER, pramipexole IR, ropinirole IR, rotigotine, and ropinirole PR with conclusions of “efficacious” and “clinically useful” for all. Ropinirole PR and rotigotine (see earlier) were evaluated in open‐label extension studies of prior double‐blind RCTs; the quality of these studies was not scored, but they were considered for new safety issues, of which none were reported.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…A total of 3 studies were evaluated. We excluded a trial where apathy was not an inclusion criterion .…”
Section: Results and Conclusionmentioning
confidence: 99%
“…One high‐quality trial on rotigotine had negative outcomes with some effects on post hoc analyses, and thus the efficacy conclusion is “ unlikely efficacious” and the practice implication “ investigational.”…”
Section: Results and Conclusionmentioning
confidence: 99%
“…Apathy related items including “lost interest in surroundings” and “lost interest in doing things” showed the greatest effect sizes. A more recent investigation of rotigotine showed no effect on apathy as rated by patients or caregivers, despite some improvements in clinical apathy scores [74]. This may signal difficulties in patients’ ability to accurately qualify their apathetic status and subsequent changes.…”
Section: Apathymentioning
confidence: 99%